2006
DOI: 10.1017/s002221510600510x
|View full text |Cite
|
Sign up to set email alerts
|

Securing a paediatric airway with a nasal sucker for laser surgery

Abstract: The administration of anaesthetic gases to an infant undergoing an endolaryngeal laser procedure can be difficult. We describe the use of a Magill's nasal sucker and an anaesthetic connector to maintain anaesthesia during laser surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Vaghela et al . described a method of administering volatile anesthetic into an infant's airway through a nasal suction device while endolaryngeal laser surgery proceeded. It has also been reported that anesthesia can be maintained with insufflation of oxygen and 5% halothane or 8% sevoflurane via a nasopharyngeal tube in spontaneously breathing patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaghela et al . described a method of administering volatile anesthetic into an infant's airway through a nasal suction device while endolaryngeal laser surgery proceeded. It has also been reported that anesthesia can be maintained with insufflation of oxygen and 5% halothane or 8% sevoflurane via a nasopharyngeal tube in spontaneously breathing patients .…”
Section: Discussionmentioning
confidence: 99%
“…Airway management for laryngeal endoscopic surgery usually involves one of four methods: controlled mechanical ventilation, jet ventilation, apnea with intermittent ventilation, and spontaneous breathing . The spontaneously breathing anesthesia technique involves oxygen insufflation: through an endotracheal tube positioned superior to the glottis along the lateral portion of the laryngeal endoscope , through a nasal suction device or nasopharyngeal catheter . With this anesthetic technique, however, one cannot accurately monitor endtidal carbon dioxide tension (PetCO 2 ) due to the presence of an open airway .…”
Section: Introductionmentioning
confidence: 99%